Fixed bed adsorption column studies and models for removal of ibuprofen from aqueous solution by strong adsorbent Nano-clay composite - Rafati, Lida (J Environ Health Sci Eng, 2019)
In this study, ibuprofen was removed using a strong nano-clay-composite based on cloisite 15A, PVP and β-cyclodextrin (CD@clay-PVP) adsorbent through a fixed-bed column system. Chemically modified nano-clay was characterized by using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and XRD. Different input situations were evaluated and included adsorbent bed height, initial concentrations, and the impact of the flow rate on the adsorbent. The various mathematical models employed to predict the breakthrough curve and model parameters include Thomas, bed-depth service time (BDST), Yoon–Nelson, and Clark. The characteristics of parameters related to the models were obtained by linear and nonlinear regression to design the process for the columns. Based on error analysis and adsorption conditions, all of the models are identical in describing the adsorption fixed-bed columns.